PEMANFAATAN TEKNOLOGI SEBAGAI MEDIA PEMMBELAJARAN EFEKTIF DALAM MENDUKUNG IMPLEMENTASI OUTCOME-BASED EDUCATION (OBE) DI SMA NEGERI 4 BONE - Ilham; Mutmainna, Andi; Kalista, A; Gustiana, Feby; Mulianto, Astiana; Abdullah, Erwin; Rais, Supirman; Afandi, Feri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of Outcome-Based Education (OBE) in the Merdeka Curriculum requires teachers to conduct measurable and student-centered learning evaluations. However, teachers still face difficulties in monitoring individual student achievement, maintaining student engagement, and conducting efficient assessments during classroom learning. This study aims to analyze the utilization of technology as an effective learning medium in supporting the implementation of OBE at SMA Negeri 4 Bone. The study employed a descriptive qualitative approach using field observation data derived from PLP II reports, classroom observations, teaching practices, and learning documentation. Data collection techniques included participatory observation, documentation, and analysis of teaching modules and learning media. The findings indicate that the use of Smart TV, PowerPoint presentations, instructional videos, Quizizz, and Google Forms enhanced student participation, increased learning interaction, and facilitated teachers in conducting formative assessments. Digital assessment platforms also enabled teachers to identify students’ learning outcomes more accurately through KKTP-based evaluation and remedial classification. Therefore, technology utilization not only functions as a visual aid but also becomes a strategic instrument in supporting data-based learning evaluation within the OBE framework.